ATRX mutations and glioblastoma: Impaired DNA damage repair, alternative lengthening of telomeres, and genetic instability. (3rd May 2016) - Koschmann, Carl; Lowenstein, Pedro R.; Castro, Maria G.
ABSTRACT: Alpha thalassemia/mental retardation syndrome X-linked ( ATRX ) is mutated in nearly a third of pediatric glioblastoma (GBM) patients. We developed an animal model of ATRX-deficient GBM. Using this model combined with analysis of multiple human glioma genome-wide datasets, we determined that ATRX mutation leads to genetic instability, impaired non-homologous end joining, and alternate lengthening of telomeres (ALT).